'These streets are ours': Mumbai's urban form and security in the vernacular. (4th May 2017) - Gupte, Jaideep
Abstract: This article contributes to the growing literature on the spatial dynamics of urban violence in the developing world. It highlights the dialectic between urban form, violence and security provision as vernacular in nature, shaped by hyperlocal processes and actors. And yet, this dialectic is dominated by state and military-centred terminology, and continually underpinned by the state's imposition of order to constitute the city as a site for legitimate control. This materialises as the often arbitrary recognition of one area as 'at the margins', and not another, as the recognition of one group of people as 'slum dwellers' or illegal residents, and not others, or as the recognition of some individuals as criminal, and not others. Using detailed case study material from a group of inner-city neighbourhoods in Mumbai, India, the article suggests that urban form in its physical, political and historical characterisations not only influences how vigilante protection operates, but also interacts in a non-benign manner with the mechanics by which the state endeavours to control violence. As such, it shapes who is vulnerable to violence, how vulnerable they are, and why. This speaks directly to the nature of security provision witnessed across the cities of the developing world.